2018
DOI: 10.1111/risa.13009
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Approach to Risk Assessment Based on Species Sensitivity Distributions

Abstract: The guidelines for setting environmental quality standards are increasingly based on probabilistic risk assessment due to a growing general awareness of the need for probabilistic procedures. One of the commonly used tools in probabilistic risk assessment is the species sensitivity distribution (SSD), which represents the proportion of species affected belonging to a biological assemblage as a function of exposure to a specific toxicant. Our focus is on the inverse use of the SSD curve with the aim of estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…The screening standards of toxicity data used in the study were based on the strict rules as detailed in Text S1. The lethal concentration affecting 50% of individuals (LC50) or the effective concentration affecting 50% of individuals (EC50) were selected as the acute toxicity endpoint (Wang et al, 2017a), while the no observed effect concentration (NOEC) or the lowest observed effect concentration (LOEC) were selected as the chronic toxicity endpoint (Monti et al, 2018). The species mean acute/ chronic value (SMAV/SMCV) was calculated by use of geometric means when more than one toxicity data for the same species were available (Stephen et al, 1985).…”
Section: Toxicity Data Setsmentioning
confidence: 99%
“…The screening standards of toxicity data used in the study were based on the strict rules as detailed in Text S1. The lethal concentration affecting 50% of individuals (LC50) or the effective concentration affecting 50% of individuals (EC50) were selected as the acute toxicity endpoint (Wang et al, 2017a), while the no observed effect concentration (NOEC) or the lowest observed effect concentration (LOEC) were selected as the chronic toxicity endpoint (Monti et al, 2018). The species mean acute/ chronic value (SMAV/SMCV) was calculated by use of geometric means when more than one toxicity data for the same species were available (Stephen et al, 1985).…”
Section: Toxicity Data Setsmentioning
confidence: 99%
“…The NOEC was criticized for having no biological meaning because it is not a measure of toxicity but rather of nontoxicity. The NOEC considerably depends on the study design that can lead to higher variability (Laskowski 1995;Isnard et al 2001;Jager 2012;Fox and Landis 2016;Monti et al 2018). Thus, the measure of ECx was proposed to replace the NOEC, whereas the selected value for x depends on jurisdiction and risk management objectives (Isnard et al 2001;Beasley et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the biological community does not necessarily follow 1 single distribution (Xu et al 2015). Nonparametrical SSD approaches have been developed to tackle this challenge (Newman et al 2000;Wang et al 2015;Monti et al 2018). One of these approaches is the probabilistic species sensitivity distribution (PSSD) (Gottschalk and Nowack 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations